1999
DOI: 10.1021/ac9903757
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Separations of Electrosprayed Peptide Libraries

Abstract: High-resolution ion mobility spectrometry has been combined with time-of-flight mass spectrometry for analysis of a combinatorial peptide library that is expected to contain 676 components. In this approach, the components of a mixture of three residue peptides, having the general form (D)Phe-Xxx-Xxx-CONH2 (where Xxx is randomized over 26 residues including 10 naturally occurring amino acids and 16 synthetic forms) were ionized by electrospray ionization. Ion mobility/time-of-flight distributions have been rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
151
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(155 citation statements)
references
References 41 publications
(74 reference statements)
4
151
0
Order By: Relevance
“…Both CID datasets are consistent with the Asn-Tyr-Val-Phe having a precursor ion that has been modified by a chemical group that shifts the mass by 56 a. We have previously identified this mass shift as evidence that a t-butyl side chain protecting group is not completely removed during the final deprotection steps of the synthesis [6]. Examination of many frames in the mixture indicates that greater than 90% of peptides containing a Tyr in the sequence exhibit this 56 a shift in the precursor ion mass.…”
Section: Evidence For a Synthetic Failuresupporting
confidence: 61%
See 1 more Smart Citation
“…Both CID datasets are consistent with the Asn-Tyr-Val-Phe having a precursor ion that has been modified by a chemical group that shifts the mass by 56 a. We have previously identified this mass shift as evidence that a t-butyl side chain protecting group is not completely removed during the final deprotection steps of the synthesis [6]. Examination of many frames in the mixture indicates that greater than 90% of peptides containing a Tyr in the sequence exhibit this 56 a shift in the precursor ion mass.…”
Section: Evidence For a Synthetic Failuresupporting
confidence: 61%
“…We have shown that it is possible to separate many different isomer types, including sequence-, structural-and stereo-isomers. 6 A key aspect of the separation is simply that different isomers establish different conformations (having different collision cross sections) in the gas phase.…”
mentioning
confidence: 99%
“…Ion mobility has been used extensively to separate ions of small organic molecules in the gas phase on the basis of collision cross section-to-charge ratios (⍀/z) [11][12][13][14][15][16]. IM/MS has been used to determine the conformations of mass identified peptide and protein ions as well to investigate the gas-phase dynamics of biological molecules [17][18][19][20]. Recently, ESI [14,15] and MALDI [10] have been used in combination with IM drift cells.…”
mentioning
confidence: 99%
“…This is interesting because the trans-addition of the PEG arm does not significantly alter the shape of the europium complex. The 2-and 1-arm Eu-PEG products having closely related shapes provides an explanation for difficulties in purification using SEC, highlighting the utility of using three-dimensional separation by charge, size, and shape inherent to IMS [54,72].…”
Section: Ims Separationmentioning
confidence: 98%